2008
DOI: 10.1152/ajpendo.90264.2008
|View full text |Cite
|
Sign up to set email alerts
|

Receptor-dependent prorenin activation and induction of PAI-1 expression in vascular smooth muscle cells

Abstract: Although elevated plasma prorenin levels are commonly found in diabetic patients and correlate with microvascular complications, the pathological role of these increases, if any, remains unclear. Prorenin/renin binding to the prorenin/renin receptor [(p)RR] enhances the efficiency of angiotensinogen cleavage by renin and unmasks prorenin catalytic activity. We asked whether plasma prorenin could be activated in local vascular tissue through receptor binding. Immunohistochemical staining showing localization of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
63
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(71 citation statements)
references
References 36 publications
8
63
0
Order By: Relevance
“…25 It is interesting to note that this receptor has also been found to activate prorenin. [25][26][27][28][29] After binding to the (P)RR, prorenin undergoes a conformational change in the prosegment region, thus opening the active site accessible to the substrate angiotensinogen (Figures 1 and 2). The (P)RR mRNA has been reported to express in many organs, for example the kidney, heart, brain, eye, adipose tissue and vascular smooth muscle cells, 25,34 and thus it may help to accumulate renin and prorenin locally in tissues even though lacking components of RAS, that is, in the heart and vasculature wall.…”
Section: The Interaction Of Renin/prorenin With the (P)rrmentioning
confidence: 99%
See 2 more Smart Citations
“…25 It is interesting to note that this receptor has also been found to activate prorenin. [25][26][27][28][29] After binding to the (P)RR, prorenin undergoes a conformational change in the prosegment region, thus opening the active site accessible to the substrate angiotensinogen (Figures 1 and 2). The (P)RR mRNA has been reported to express in many organs, for example the kidney, heart, brain, eye, adipose tissue and vascular smooth muscle cells, 25,34 and thus it may help to accumulate renin and prorenin locally in tissues even though lacking components of RAS, that is, in the heart and vasculature wall.…”
Section: The Interaction Of Renin/prorenin With the (P)rrmentioning
confidence: 99%
“…Batenburg et al 27 found a similar activation of human prorenin by binding to the human (P)RR with 6.0 nmol l À1 of K D , using the receptor expressed in smooth muscle cells of transgenic rat for this receptor. Zhang et al 28 reported the activation of rat prorenin after binding to rat (P)RR expressed in the cultured vascular smooth muscle cells.…”
Section: Blood Vesselmentioning
confidence: 99%
See 1 more Smart Citation
“…[5][6][7][8][9][10][11][12] In vitro studies using small interfering RNA have been demonstrated that knockdown of (P)RR suppressed fibrotic factor release in rat cultured vascular smooth muscle cells and mesangial cells. 28,29 Moreover, the (P)RR has been reported to cause nonproteolytic activation of prorenin and directly activate intracellular signaling pathways independently of the RAS. 1,30 Saris et al 31 reported that prorenin-induced intracellular signaling in cardiomyocytes independently of angiotensin II and suggested that prorenin directly affected cardiac growth and development via the (P)RR-mediated activation of ERK1/2.…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that (P)RR expressed in VSMCs in human (P)RR transgenic rats can be recycled between intracellular compartment and cell membrane (Batenburg et al, 2007). The (P)RR is also localized on the membrane of stromal adipose cells (Achard et al, 2007), in the neurons of neonatal rats (Shan et al, 2008), on COS-7 cells (Nabi et al, 2007), in glomerular mesangial cells, the subendothelium of renal arteries, podocytes, and distal nephron cells (Nguyen et al, 2002(Nguyen et al, , 1996(Nguyen et al, , 1998 of human and rat kidneys; U937 monocytes (Feldt et al, 2008b) and also in intracellular compartments or on the surface of vascular smooth muscle cells (VSMCs) Zhang et al, 2008), in endoplasmic reticulum (Schefe et al, 2006;Yoshikawa et al, 2011), golgi apparatus Yoshikawa et al, 2011), cytosol Cousin et al, 2009) and found in plasma (Cousin et al, 2009). Expression of (P)RR is also categorized in the subfornical organ (SFO), paraventricular nucleus, the supraoptic nucleus, the nucleus of the tractus solitarius (NTS), or the rostral ventrolateral medulla regions of brain that were believed to be involved in the central regulation of cardiovascular function and volume homeostasis , in the frontal lobe of human brain and pituitary (Takahashi et al, 2010).…”
Section: (Pro)renin Receptor a New Family Member Of Renin Angiotensimentioning
confidence: 99%